Moringa leaf extract as a natural alternative for the growth, yield, and yield components of onion (Allium cepa L.) varieties in central Gondar, North Ethiopia - Marie, Gizachew; Tagele, Aleminew; Kinfu, Simegn (Frontiers in Sustainable Food Systems, 2025)
IntroductionOnion (Allium cepa L.) is an important bulb crop. These allium species grow in most areas of central Gondar. However, lack of researcher based recommendation of moringa leaf extract (MLE) for onion production and improved varieties of onion are some of the problems.MethodsRandomized complete block design with 3×5 combinations of three varieties (Nafis, Adama Red and Bombay Red) and four different levels of MLE concentration (0, 2, 4, 6% and one level of kinetin (2mg/l)) with three replications were used.Results and discussionVarieties showed significant (p < 0.05) variation on most growth, yield and quality parameters except dry matter. The highest leaf number (14.03), bulb diameter (7.06cm), TSS (13.99 oBrix) and late 80% days to maturity (118.02 days) were recorded from Nafis while the lowest was recorded from Bombay Red. Foliar application of MLE (6%) gave the highest leaf number, leaf diameter, bulb diameter, dry matter, TSS and was late to mature compared to control. Nafis variety coupled with spray of MLE (6%) resulted in significantly higher plant height, bulb weight and marketable yield (90 cm, 96.22 g, and 23.13 t ha−1) followed by Nafis variety sprayed with MLE (4%). The partial budget analysis revealed that Nafis variety sprayed with MLE (6%) resulted in yield increment which does not compensate for the increased cost. In addition, MRR observed on Nafis variety sprayed with MLE (4%) was above the acceptable range. Hence, it can be concluded that Nafis variety combined with foliar application MLE (4%) can enhance the growth and productivity of onion.